Chemically Functionalized Two‐Dimensional Carbon Materials. Issue 15 (17th July 2020) - Sekiya, Ryo; Haino, Takeharu
Abstract: Nanographenes (NGs), also known as graphene quantum dots, have recently been developed as nanoscale graphene fragments. These nanocarbon species can be excited with UV light and emit light from the UV‐to‐visible region. This photoemission has received great attraction across multiple scientific fields. NGs can be produced by cutting off carbon sources or fusing small organic molecules to grow graphitic structures. Furthermore, the organic synthesis of NGs has been intensely studied. Recently, the number of research papers on postsynthetic modification of NGs has gradually increased. Installed organic groups can tune the properties of NGs and provide new functionalities, opening the door for the development of sophisticated carbon‐based functional materials. This review sheds light on recent progress in the postsynthetic modification of NGs and provides a brief summary of their production methods. Abstract : Postsynthetic modification of nanographenes allows the development of sophisticated carbon‐based functional materials. This review focuses on the recent advances in postsynthetic modifications of nanographenes and related carbon species, in particular edge functionalization.